2013
DOI: 10.1080/03069885.2012.729025
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of parent counselling in eating disorders

Abstract: Eating Disorders (ED) are often severe illnesses entailing a heavy burden for families. Family therapy is recommended for young patients, but only a few studies have investigated therapeutic interventions with families tailored also to adult and longstanding patients. We recruited 87 families with daughters affected by an ED, aiming to assess the effectiveness of eight sessions of parent counselling. The primary outcome was the improvement of parents' coping abilities to achieve more effective support skills. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 79 publications
(101 reference statements)
0
5
0
Order By: Relevance
“…There is also preliminary evidence that longstanding carers of people with ED (i.e. carers of SEED) could benefit from individual counselling (Abbate- Daga et al, 2013). Further research on carers of people with SEED is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…There is also preliminary evidence that longstanding carers of people with ED (i.e. carers of SEED) could benefit from individual counselling (Abbate- Daga et al, 2013). Further research on carers of people with SEED is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…The purpose for parent counselling is to inform, educate and provide emotional support to the patient and the family. The study by Abbate-Daga et. al., (2013) looked at a three-step intervention whereby two weeks prior to treatment, parents participated in a preliminary informative group, then parents were clinically assessed, followed by the parents attending counselling for eight 60-minute sessions.…”
Section: Parent Counsellingmentioning
confidence: 99%
“…Carers of family members who have an eating disorder are uncertain about how to help, expressing their burden and need for information. Studies have shown that carers of those with Family Therapy in the Treatment of Eating Disorders eating disorders are clinically anxious and/or depressed (Abbate-Daga et al, 2013;Treasure, Whitaker, Todd, & Whitney, 2012). Therefore, the carer's own symptomatology and uncertainty about helping can exacerbate the symptoms and behavior of the individual with the eating disorder.…”
Section: Parent Counsellingmentioning
confidence: 99%
See 2 more Smart Citations